Gender Development Studies: The Role of Gender Development in Poverty Reduction Efforts in Central Java Province - Kardiman, Maman Eka; Pratama, Crismon Alfajri Agus (Jurnal Planologi, 2025)
Inequality in power relations in the context of gender development and empowerment causes women to fall into the category of vulnerable and cannot be empowered to the fullest. The patriarchal view of women only doing domestic work has led to women's low contribution to economic development and low poverty reduction. In the last decade, despite the implementation of gender development efforts, Central Java Province is still categorised as the second poorest province in Java. This study aims to understand the role of gender in poverty reduction efforts in Central Java Province. This research method is conducted using multiple linear regression analysis and PGCA and presented using GIS to see comparisons between regions. The findings of this study show that the growth of 0.70 GDI, 0.035 GEI and 0.91WCI has an effect on a 1% reduction in poverty in Central Java Province as shown through the FEM model POOR = -0.707551GDI - 0.035017GEI - 0.917119WIC - 0.465785WDR + 0.050154WAGEG. Furthermore, this study also shows that there are still inequalities in the GDI, GEI and WCI variables which indicate that gender development and empowerment efforts in Central Java Province are not yet optimal.